OC-065 Targeted inhibition of tissue factor and thrombin on CD31 expressing cells suppresses hepatic fibrosis in CCl4 treated mice. (28th May 2012) - Petts, G; Dhar, A; Kudo, H; Sadiq, F; Anstee, Q; Kallis, Y; Dorling, A; Goldin, R; Thursz, M
Abstract : Introduction: Recent evidence suggests a role for the coagulation cascade in promoting liver fibrosis. However, the cellular basis for this relationship is unclear. In order to explore this relationship we employed two unique transgenic mice strains expressing membrane–tethered tissue factor pathway inhibitor (TFPI) or hirudin (anti-thrombin) fusion proteins driven by a CD31 promoter. These strains allow for the selective inhibition of tissue factor (TF) or thrombin on endothelial cells, monocytes and platelets expressing CD31. Aims: To evaluate the impact of the targeted inhibition of tissue factor and thrombin on effector cells of liver fibrosis in murine hepatic fibrosis induced by CCl4 . Methods: Liver fibrosis was induced in CD31-TFPI, CD31-Hirudin and wild type control mice with 4 weeks carbon tetrachloride (CCl4 ) administered by intraperitoneal injection. Animals were culled and livers extracted for histological and biochemical analysis. Fibrosis was scored using a four point semi-quantitative system and quantified by digital image analysis to determine percentage area of fibrosis. Immunohistochemistry to determine α-SMA expression, a marker of hepatic stellate cell activation was performed and the mean number of activated stellate cells was quantified per high power field. Results: The percentage area of fibrosis was significantly less in CD31-TFPI (1.89%±0.26, p=0.001) and CD31-Hirudin mice (1.04%±0.16, p=0.00003) in comparison to control mice (3.66%±0.39). Semiquantitative fibrosis scoring showed a significant difference between the CD31-TFPI (median 2/4) and CD31-Hirudin (median 3/4) mice in comparison with control mice (median 3/4, p=0.009) but the difference between the two transgenic strains was not significant. Both transgenic strains demonstrated a significantly reduced mean number of α-SMA stellate cells per high power field in comparison to control mice (CD31-TFPI vs control, 7.4 vs 29.4, p=0.0002; CD31-hirudin vs control, 5.25 vs 29.4, p=0.0002). Conclusion: CD31 targeted inhibition of TF and thrombin significantly reduces liver fibrosis and stellate cell activation in a murine CCl4 model. The data supports the use of this novel murine model as a tool for investigating the cellular biology of the role of coagulation in liver fibrogenesis. It will also provide information for developing new treatments of human liver fibrosis. Competing interests: None declared.